Muslim Ummah in facing the challenges of globalization - Abdul Razak, Mohd Abbas; Muhamad Shukri, Abdul Salam (2017)
This presentation on globalization among others discusses the nature and differences that exist between the modern and Muslim concepts of globalization. Since it is not possible for the Muslims to live in total isolation from the things that are happening in a globalized world, they can at least come up with a strategic plan in how to position themselves in dealing with the issues and problems related to globalization. Besides that, this presentation also highlights the ideal scenario that should be prevalent in the Muslim world that can be beneficial for the Muslims as well as for others who share the space with them in this world. In realizing how the internet and social media have been wrongfully used in a globalized world, the presenters suggest on how the Muslims can use them in a productive and ethical manner. The last thing that this presentation intends to highlight is the philosophy of co-existence which should be given due consideration by people of different civilizations that live on this planet. It is the conviction of the presenters that people of different civilizations can learn all that are positive from one another and can live in peace and harmony.